Neighborhood environment — formation of a health-saving human ecosystem - Yu. V. Rodionova (Кардиоваскулярная терапия и профилактика)
See “Neighborhood environment: the impact of alcohol and tobacco outlets availability on health of people living in a certain area” Antsiferova A. A., Kontsevaya A. V., Mukaneeva D. K., Drapkina O. M. in Review articles, pp. 84-91.